Technique and initial results of fully robotic left hepatectomy for malignant tumor: an alternative minimally invasive method to the laparoscopic approach - Sucandy, Iswanto; Tsung, Allan (Laparoscopic Surgery, 2018)
Hepatic resections are widely performed for both benign and malignant liver pathology. Outcomes of hepatic resection have improved in the last decade with better understanding of liver anatomy, advancement in surgical instrumentation, improved anesthesia care, and better perioperative patient management (1).